Bridge leadership : connecting educational leadership and social justice to improve schools - Tooms, Autumn K.; Boske, Christa (Educational leadership for social justice., 2010)
This is the first chronicle of the history of social justice as a line of inquiry within the field of educational administration. Editors Tooms and Boske have amassed a collective voice of leaders in the field of Educational Administration who have broken barriers and expanded the field through their own work and scholarship within a national and international arena. Many of these narratives are the first time tellings of the challenges and successes found in the works of this group of scholars of historic significance.This collection is written and organized into practical and easy to digest sections. They are part history lesson, and part practical teaching tool for those who prepare school leaders. Anyone from school leaders to academics interested or charged with unpacking the messy intersections between school leadership and issues of social justice will find inspiration and easy to understand explanations of leadership and equity work within the chapters presented.